PENERAPAN MODEL COOPERATIVE LEARNING TYPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS - Robina Simanjuntak (STKIP ROKANIA, 2017)
This study discusses the application of cooperative learning type STAD model to improve the learning outcomes of IPS students of class VI SD Negeri 003 Rambah Year lesson 2014 / 2015. Subjects in this study amounted to 25 people consisting of 14 men and 11 women who are students of the class VI academic year 2014/2015. STAD cooperative learning type model proved to improve student learning outcomes from the average class 66.7 to 74.4 in the first cycle and 77.4 in cycle II. Percentage improvement of completeness in cycle I is 80% while in cycle II the percentage of completeness increase of 88%